Engagement and optimism in a group of Colombian workers: analysis of some predictors - Ocampo Álvarez, Luisa Fernanda; Quiroz-González, Eliana Fernanda; Villavicencio-Ayub, Erika (Universidad y Salud, 2021)
Introduction: Engagement and optimism contribute to mental health. Therefore, it is important to carry out research on these psychological phenomena that are poorly studied in Colombia. Objective: To analyze the relationship between engagement and optimism in a group of Colombian workers and identify the role of age and job seniority in predicting these two phenomena. Materials and methods: An associative strategy was applied, with the participation of 298 workers (124 men and 174 women) from a Telecommunications company. The Utrecht Work Engagement Scale-17 and Life Orientation sociodemographic questionnaires were used. The hypothesis was tested through Pearson correlation, variance analysis, and multiple linear regression model with successive steps. Results: The engagement dimensions correlated with optimism (vigor (r=0.42, p<0.01), commitment (r=0.26, p<0.01) and absorption (r=0.20, p<0.01)). Overall, there were differences between commitment in reference to age (p=0.01) and seniority (p=0.04). Predictive models showed associations between age and vigor (β=0.25, t=4.2, p<0.000), commitment (β=0.202, t=3.38, p<0.001) and absorption (β=0.145, t=2.4, p<0.017). Conclusions: There is a positive relationship between engagement and optimism. Based on this study, even though age is a predictor of engagement, it does not play the same role for optimism.